Noncoding RNAs in cancer and cancer stem cells - Huang, Tianzhi (Sun Yat-sen University Cancer Center, 2013)
In recent years, it has become increasingly apparent that noncoding RNAs (ncRNA) are of crucial importance for human cancer. The functional relevance of ncRNAs is particularly evident for microRNAs (miRNAs) and long noncoding RNAs (lncRNAs). miRNAs are endogenously expressed small RNA sequences that act as post-transcriptional regulators of gene expression and have been extensively studied for their roles in cancers, whereas lncRNAs are emerging as important players in the cancer paradigm in recent years. These noncoding genes are often aberrantly expressed in a variety of human cancers. However, the biological functions of most ncRNAs remain largely unknown. Recently, evidence has begun to accumulate describing how ncRNAs are dysregulated in cancer and cancer stem cells, a subset of cancer cells harboring self-renewal and differentiation capacities. These studies provide insight into the functional roles that ncRNAs play in tumor initiation, progression, and resistance to therapies, and they suggest ncRNAs as attractive therapeutic targets and potentially useful diagnostic tools.